PASSADO E PRESENTE EM TEXTOS TECIDOS POR MULHERES: DO PROCESSO HISTÓRICO DE SUBORDINAÇÃO DAS MULHERES À ESCALADA DE MARIA FIRMINA DOS REIS E A LITERATURA AFRO-BRASILEIRA: PAST AND PRESENT IN TEXTS WRITTEN BY WOMEN: FROM THE HISTORICAL PROCESS OF WOMEN’S SUBORDINATION TO THE CLIMB OF MARIA FIRMINA DOS REIS AND AFRO-BRAZILIAN LITERATURE - Sousa , Larissa da Silva (Revista Decifrar, 2024)
This research reflects the intellectual trajectory of Maria Firmina dos Reis, based on the elaboration of a literary tradition of Brazilian women. It aims to reflect on the path that women writers took from the 19th century to the Editora Mulheres project and the rise of Maria Firmina as an exponent of Afro-Brazilian literature. For its construction, we resorted to research that ranges from women’s history to recent studies on the concept of Afro-Brazilian literature, for this we used studies by DEL PRIORE (2009); PERROT (2009); DUARTE (2011); SOUZA (2006), among others. It is evident from this study that women needed to travel a route composed of many challenges, especially black women, to rise as writers and intellectuals in Brazil and that studies that deal with them are increasingly necessary and growing in Brazilian universities.